2017
DOI: 10.1177/1940161217740696
|View full text |Cite
|
Sign up to set email alerts
|

Mediated Leader Effects: The Impact of Newspapers’ Portrayal of Party Leadership on Electoral Support

Abstract: Conventional wisdom holds that party leaders matter in democratic elections. As very few voters have direct contact with party leaders, media are voters’ primary source of information about these leaders and, thus, the likely origin of leader effects on party support. Our study focuses on these supposed electoral effects of the media coverage of party leaders. We examine the positive and negative effects of specific leadership images in Dutch newspapers on vote intentions. To this end, we combine an extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 78 publications
0
14
0
3
Order By: Relevance
“…Fuente: elaborado a partir de Manrique-Grisales (2020, p. 148). elementos correspondientes a cada categoría (agenda setter, agenda setting y niveles de discurso) 1 .…”
Section: Figura 1 Representación Del Mhdunclassified
See 1 more Smart Citation
“…Fuente: elaborado a partir de Manrique-Grisales (2020, p. 148). elementos correspondientes a cada categoría (agenda setter, agenda setting y niveles de discurso) 1 .…”
Section: Figura 1 Representación Del Mhdunclassified
“…Desde el siglo xix los periódicos se han convertido en la principal fuente de información sobre los acontecimientos económicos, políticos y sociales en todo el mundo. En la actualidad, los periódicos no solo cumplen un papel informativo, sino que también influyen en la toma de decisiones gubernamentales o administrativas (Gentzkow et al, 2009; Owen, 2019) y en la opinión pública sobre asuntos de interés general (Aaldering et al, 2018;Coppock et al, 2018;Hameleers, 2019;Lundberg, 1926;Meo, 2017). Por esta razón, desde hace décadas se ha estudiado la influencia de la prensa en la población con fines sociológicos, publicitarios, políticos o propagandísticos (Lundberg, 1926; Casals-Carro, 2009; Allen & Sieczkiewicz, 2010; Tanacković et al, 2014).…”
Section: Introductionunclassified
“…The personalization literature which relies on computer-assisted content analysis mainly consists in searching for media contents that contain at least one of the words of a pre-specified lexicon within a certain linear distance to the politician under scrutiny (Aaldering, van der Meer, & Van der Brug, 2018;Aaldering & Vliegenthart, 2016;Hollanders & Vliegenthart, 2011). Nevertheless, for identifying the words in a sentence which are actually attributed to a given target, linear n-grams in the sense of adjacent strings of tokens, parts of speech, etc.…”
Section: Preprocessing Proceduresmentioning
confidence: 99%
“…In half of the 20 elections explored, the research concluded that leaders were possibly decisive to the election outcome (also see Garzia, 2012Garzia, , 2013. The indirect effects of leaders on vote choice have been championed by media scholars, with research showing media coverage influences voters' perceptions of leaders (e.g., Bos et al, 2011;Eberl et al, 2017;Gidengil and Everitt, 2003), and how this can mediate the extent of leaders' impact on the vote (Aaldering et al, 2018;Kleinnijenhuis et al, 2019).…”
Section: Identifying Leader Inclined Voting Personalization Of Politics: State Of the Artmentioning
confidence: 99%